Genetic Diversity of a Natural Population of Akebia trifoliata (Thunb.) Koidz and Extraction of a Core Collection Using Simple Sequence Repeat Markers - Zhong, Yicheng; Wang, Yue; Sun, Zhimin; Niu, Juan; Shi, Yaliang; Huang, Kunyong; Chen, Jing; Chen, Jianhua; Luan, Mingbao (Frontiers in Genetics, 2021)
Understand genetic diversity and genetic structure of germplasm is conservation and utilization premise of germplasm. And core coleectin can reduce the cost and difficulty of germplasm conservation. Akebia trifoliata (Thunb.) Koidz is an important medicinal, fruit and oil crop, particularly in China. In this study, 28 simple sequence repeat (SSR) markers were used to assess the genetic diversity and genetic structure of a natural population of A. trifoliata, including 955 germplasms, to determine their molecular identity and to extract a core collection. The genetic diversity of the natural population was moderately polymorphic. The average number of alleles (Na), observed heterozygosity (HO), expected heterozygosity (HE), Shannon’s information index (I*), and polymorphic information content (PIC) were 3.71, 0.24, 0.46, 0.81, and 0.41, respectively. Four subpopulations were identified, indicating a weak genetic structure. 955 germplasms caould be completely distinguished by the characters of s28, s25, s74, s89, s68, s30, s13, s100, s72, s77, and s3. And each germplasm's molecular identiyy was made up of eleven characters. The core collection was composed of 164 germplasms (17.2% of 955 total germplasms in the population) and diversity parameters differed significantly from those of a random core collection. These results have implications for germplasm conservatio. At the same time, based on the results, the 955 germplasm could be better used and managed